Key performance indicators used by dairy consultants during the evaluation of reproductive performance during routine visits - Armengol, Ramon; Fraile, Lorenzo; Bach, Alex (Frontiers in Veterinary Science, 2023)
Dairy farms need thorough and efficient control on reproduction. Consultants specialized on reproduction use key performance indicators (KPI) to monitor the reproductive performance of the farms and must be able to decipher between the approach in a first visit, and routine visits. Forty-nine consultants specialized in dairy reproduction from 21 countries responded to an online survey conducted to determine the most suitable parameters in a routine visit every 2 to 4 weeks. The survey was comprised of 190 questions, 178 of them rated from 0 (irrelevant) to 10 (maximum importance) points. The questions were divided into 5 sections: 1) consultant and farm model, 2) general data of the farm, 3) cow reproduction, 4) postpartum and metabolic disease, and 5) heifer reproduction. The median, interquartile range, minimum and maximum values and 95% confidence interval were determined for each question. A multivariate analysis, using between-group linkage via Ward´s hierarchical clustering was conducted to generate clusters of consultants according to their response pattern. Lastly, a Chi-square test was conducted to assess the association between years of experience of the consultant and farm size within the clusters generated in each section of the questionnaire. The majority of the consultants considered 34 parameters to be highly important (rate 8-10) to analyze during routine visits. Consultants use several KPI to evaluate any of the presented sections and consider that all the five sections are critical to control. Consultants are aware to use KPI that reflect heat detection, fertility and farming efficiency. As well as KPI that can provide information on reproductive efficiency in the near future for cows, such as postpartum and metabolic diseases. Farm size and years of experience of the consultant did not influence the type or number of parameters chosen as KPI during routine visits. The parameters rated with the highest importance (rate 10) that could be considered for an easy, fast, and universal use in routine visits to assess the reproductive status were: First service CR (%), Overall pregnancy rate (%) for cows and age at 1st calving (d) for heifers.